Angiotensin II in Decompensated Cirrhosis Complicated by Septic Shock. (September 2020) - Coleman, Patrick J.; Nissen, Alexander P.; Kim, Daniel E.; Ainsworth, Craig R.; McCurdy, Michael T.; Mazzeffi, Michael A.; Chow, Jonathan H.
This case describes the first reported use of human-derived synthetic angiotensin II (Ang-2) in a patient with decompensated cirrhosis and septic shock. The patient presented in vasodilatory shock from Enterobacter cloacae bacteremia with a Sequential Organ Failure Assessment Score of 14 and a Model for End-Stage Liver Disease score of 36. This case is significant because liver failure was an exclusion criterion in the Angiotensin II for the Treatment of Vasodilatory Shock (ATHOS-3) trial, but the liver produces angiotensinogen, which is key precursor to Ang-2 in the renin-angiotensin-aldosterone system. Resuscitation with Ang-2 is a potentially beneficial medication when conventional vasopressors have failed to control mean arterial pressure in this population.